Peranan Internal Audit Dalam Pengendalian Internal Piutang Pada PT. Pos Indonesia Persero Cabang Depok - Fatimatuzzahro, Marina; Sudaryanto, Edy (Institut Bisnis dan Informatika Kesatuan, 2019)
Internal Audit functions to assess the results of the activities of an organization. The assessment consists of assessing organizational structure, planned activities, policies, employee performance, and compliance with procedures. Internal Audit is needed in organizations or companies that are engaged in production and services, to direct the company's operations, prevent the use of the system, and protect accounts receivable. Internal audit works independently on the company by conducting checks and evaluations that produce suggestions in the form of improvements to the management and control of the entities examined in this case are receivables. The purpose of this study was to find out how the role of internal audit, to solve problems and the efforts made in internal control of receivables at PT. Pos Indonesia Persero Depok Branch. The research method used is descriptive qualitative, by collecting data related to existing problems in the company, in accordance with the basics of the theory studied. Data collected, used to solve existing problems. The results of the study show that internal audit implementation at PT. Pos Indonesia Persero Depok Branch has been good, so the control of accounts receivable has been running properly. Supervision of the company's performance must continue to be carried out by the internal audit so that there are no violations and improvements to the audit results are carried out according to input from the Internal audit. In addition, the internal audit should understand the activities of the auditee (the audited party), so that in conducting the audit as expected.